2018
DOI: 10.1128/aem.01066-18
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Sublethally Injured Yersinia enterocolitica, Escherichia coli O157:H7, and Salmonella enterica Serovar Enteritidis Cells after Neutral Electrolyzed Oxidizing Water Treatments

Abstract: The impact of neutral electrolyzed oxidizing (NEO) water treatments on the formation of sublethally injured , O157:H7, and serovar Enteritidis cells was evaluated. When pathogens were treated with 6% NEO water, approximately 38% of the treated population and 25% of the treated population became sublethally injured. The highest sublethally injured population was found when cultures were treated with 3% NEO water. Regardless of the NEO water concentration used, no sublethally injured O157:H7 cells were found. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…5B ). YcfR is involved in biofilm formation ( 33 ), and when treated with 6% electrolyzed oxidizing water, expression of ycfR was upregulated ( 34 ). Outer membrane protein STM14_2773 was also involved ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5B ). YcfR is involved in biofilm formation ( 33 ), and when treated with 6% electrolyzed oxidizing water, expression of ycfR was upregulated ( 34 ). Outer membrane protein STM14_2773 was also involved ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The protein bhsA has been previously established as a multistress resistance protein, and studies have shown that its deletion renders cells more sensitive to various stress factors such as acid, heat treatment, hydrogen peroxide, and cadmium [15]. bhsA also plays a crucial role in biofilm formation by reducing cell aggregation and cell surface adhesion, ultimately impeding cell-tocell and cell-surface interactions [27]. It has been suggested that the deletion of bhsA may alter the outer membrane structure, increasing cell aggregation and hydrophobicity and consequently influencing cell membrane formation [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…PCR mix was prepared as 1 μL template, 1 μL each primer (20 μM), 25 μL 2X MyTaq Red Mix (Bioline), and 22 μL sterile ddH2O for each gene according to MyTaq Red Mix protocol. PCR was performed with regard to the following conditions: initial denaturation at 95°C for 60 s, denaturation at 95°C for 15 s, annealing at 60°C for 15 s, and extension 72°C for 10 s with 35 cycles (Ledeboeret al, 2006;Lu et al, 2011;Lu et al, 2012;Salazar et al, 2013;Uhlich et al, 2013;Han et al, 2018). 1.7% agarose gel was run at 100 V for 45 min, for confirmation.…”
Section: Salmonella Isolatesmentioning
confidence: 99%